Overview of E-Banking Challenges and Prospects in India: Understanding the challenges and prospects of e-banking in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
E-banking, sometimes referred to as online banking, virtual banking, or internet banking, is asystem that makes it possible to conduct financial operations including money transfers, loan and EMIpayments, deposits, and cash withdrawals virtually using the internet. E-banking is now an integral part ofthe financial system. As compared to traditional bank branches, online banking is thought to be far moresecure. As compared to more conventional banking methods, it offers superior performance every time.The evolution of electronic banking in India is only getting started. The banking industry is evolving as aresult of increased competition and technological advancements. The research aims to highlight theimportance and challenges of e-banking. This study employed a secondary data research approach,using data drawn from online databases housing scholarly works on topics connected to electronicbanking. This research was conducted to provide an update on the state of online banking in India and toanalyse its advantages and challenges. The banking industry is reaping the benefits of e-banking byincreasing client happiness and loyalty. Banks owe to their consumers to make their lives simpler, andthis means making their services available through many distribution channels and internet options.